KARAKTERISTIK PENDERITA CEDERA KEPALA AKIBAT KECELAKAAN LALU LINTAS DARAT RAWAT INAP DI RSUD DR. H. KUMPULAN PANE TEBING TINGGI TAHUN 2010-2011 - Rohani Primasuri Damanik; Jemadi .; Rasmaliah . (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2013)
Traffic accidents is the most common cause of injury in the whole world. According to WHO (2008) traffic accident is the tenth leading cause of death in the world with 1.21 million deaths (2.1%). Head injury is the most common disease caused by traffic accidents than other injuries. In Indonesia, the head injury was ranked first in the order of the injury suffered by the victims of traffic accidents (33.2%). According to data Riskesdas (2007) there are 18.9% of traffic accident victims with head injuries. This study aimed to determine the characteristics of patients with head injury due to traffic accidents inpatients in RSUD Dr. H. Kumpulan Pane Tebing Tinggi in 2010-2011, a descriptive case series design. Population and sample is 114 patients (total sampling). Patients with head injuries due to traffic accidents with the highest proportion in the age group 16-24 years (39.5%), male (67.5%), student (32.5%), two-wheeled vehicle (66.3%), at 18.01-24.00 (33.3%), on Monday (21,9%), mild head injury (74.6%), the average treatment time 3.97 days, outpatient home care (51.8%), and own costs (52.6%). Highest CFR in 2010 (3,8%), four-wheeled or more vehicle (5,3%), at 18.01-24.00 (5,3%), and severe head injury (30%). There are significant differences in the average treatment time with the source charge (p = 0.001), average treatment time with the situation when returning (p = 0.001). Suggested to the hospital Dr. H. Kumpulan Pane Tebing Tinggi set to be complete recording of medical records, to the police in order to provide education to school/college regarding traffic rules, and the public to be careful when driving a vehicle and using standard helmets for two-wheeled riders. Keywords: Head Injuries, Traffic Accidents, Characteristics of Patient